The effects of TAFE/university articulation on the education of librarians in Australia - Richardson, Christine (Curtin University, 1999)
The thesis examines those students in the department of Information Studies at Curtin University of Technology who have articulated into the Bachelor of Applied Science (Information and Library Studies) through holding an Associate Diploma which qualifies them as paraprofessional library technicians.An analysis of students in the department over a period of ten years examines the number and characteristics of library technicians upgrading their qualifications and compares the academic performance of articulating students with those who have no previous qualifications in librarianship. This examination reveals little difference in the academic performance of the two groups. Interviews with academic staff and students reveal attitudes towards articulation, articulating students, education and the relationship between the professional and paraprofessional levels in librarianship which will need to be taken into account in future curricula and course development.